General features of public service in the law enforcement sphere in Ukraine - Komirchyi, P. O.; Комірчий, П. О. (My University, 2019)
The article is devoted to deepening the scientific knowledge on social and legal nature of public service at the law-enforcement area based on analyzing general features of the related public service in Ukraine. A particular attention in the article is paid to the analysis of approaches to understanding the features structure of public service in law-enforcement area, which are already outlined by the scientists. Considering the legal essence of public service in law-enforcement area and scientists positions according this service features, the author formulates a synthesized list of public service features at law-enforcement area in Ukraine. Статтю присвячено поглибленню наукових знань про соціально-правову природу публічної служби в правоохоронній сфері на основі аналізу загальних ознак відповідної публічної служби в Україні. Особливу увагу приділено аналізу вже викладених ученими підходів до розуміння структури ознак публічної служби в правоохоронній сфері. Зважаючи на правову сутність публічної служби в правоохоронній сфері та позиції вчених щодо ознак цієї служби, автор формулює узагальнений перелік ознак публічної служби в правоохоронній сфері в Україні.
Загальні ознаки публічної служби в правоохоронній сфері України
Keywords: features; law-enforcement function of the state; public servant; public service in the law-enforcement area; public service; правоохоронна функція держави; публічна служба в правоохоронній сфері; публічна служба; публічний службовець; функції держави